Výsledky artroplastiky podle Menona u rizartrózy - Lutonský, M; Pellar, D (Acta chirurgiae orthopaedicae et traumatologiae Cechoslovaca, 2004)
PURPOSE OF THE STUDY: Osteoarthritis of the basal joints is a frequent degenerative disease. The wide range of arthritic lesions of the first carpal metacarpal joint should be treated by targeted surgical techniques. These methods, including arthroplasty, arthrodesis and alloplasty, for use in relevant indications are available in the Department of Orthopedics at the Medical Faculty Teaching Hospital in Hradec Králové. In this study, the results of Menon's arthroplasty modified by the authors are evaluated. MATERIAL AND METHODS: The interpositional arthroplasty, first used and published by Menon in 1955, was introduced in January 2002 by the authors in the treatment of arthritic lesions, classified as stage III disease by the Eaton radiological rating system, in middle-aged, manually working women. The procedure consists of resection of the trapezium articular surface affected by osteoarthritis, tendon interposition, and the reconstruction of the articular capsule soft tissues using tenodesis of the abductor pollicis muscle tendons. Sixteen female patients were treated by our modified technique. The post-operative outcome of arthroplasty was evaluated by comparison of both hands' efficiency, with the use of the Cooney score system. RESULTS: At 2 years of follow-up, in 14 treated hands there was pain relief, improved mobility and an increase in grip strength; excellent and very good outcomes, as evaluated by the Cooney score, were achieved in 80% of the operated hands. In one patient, conversion of Menon's arthroplasty to an alloplasty with a Rubena prosthesis had to be carried out due to persistent complaints. DISCUSSION: The authors evaluate the surgical procedure used and present the reasons for their modification of the Menon's technique with the use of the long palmar muscle tendon. The choice of operative techniques for specific indications, as available in the authors' department, is discussed. The outcomes reported in this study are compared with the results published in the foreign literature. Complications and risks of this treatment are mentioned. The advantage of a partial over a total trapeziectomy is emphasized. CONCLUSIONS: The early outcomes of Menon's arthroplasty, which was indicated in manually working, middle-age female patients with stage III basal-joint osteoarthritis, are satisfactory. This precisely indicated and correctly performed technique has so far fulfilled the authors' expectations.
Keywords: Osteoarthritis; dospělí; Adult; Finger Joint; lidé; Arthroplasty; artroplastika; palec ruky; Humans; kloub prstu ruky; Thumb; lidé středního věku; osteoartróza; Middle Aged; ženské pohlaví; Female